Modified polymer optical fiber sensors for crude oil refractive index monitoring - Samavati, Z. (Springer, 2020)
The oil concentration as a petroleum quality parameter is an eternal mystery that determines the oil value. We report detection of crude oil refractive index (RI) changes by modified polymer optical fiber (POF) sensor which is prepared via removing the majority of cladding part until ~ 100Â nm thickness remains followed by the deposition of discontinuous silver (Ag) nanofilm as an inner layer (~ 20Â nm thicknesses) and coating with different shapes of zinc oxide (ZnO) nanostructures including nanoparticles and horizontally and vertically oriented nanorods as an outer layer. Upon conversion from ZnO nanoparticles to vertically oriented ZnO nanorods, the rms roughness, optical band gap, and light transmittance are varied from ~ 23 to ~ 346Â nm, ~ 3.45 to ~ 3.20Â eV, and 31 to 27, respectively. The higher sensing performance is obtained for the probe coated with vertically aligned ZnO nanorods at near-infrared wavelength and the value for intensity and wavelength sensitivity are 38Â dB/RIU and 78Â nm/RIU, respectively. This superior performance is originated from deep penetration of evanescent wave, high surface volume ratio, good crystallinity, adhesive interaction with crude oil molecules, large surface roughness, and high-order dispersion. Â© 2020, Springer Science+Business Media, LLC, part of Springer Nature.